{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

problem37_14

problem37_14 - -= ′ ′ γ and γ so 2 c x u t t t u x x...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
37.14: Multiplying the last equation of (37.21) by u and adding to the first to eliminate t gives , 1 1 2 2 x c u x t u x γ = - γ = + and multiplying the first by 2 c u and adding to the last to eliminate x gives , γ 1 1 γ 2 2 2 t c u t x c u t =
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: -= ′ + ′ ), ( γ and ) ( γ so 2 c x u t t t u x x ′ + ′ = ′ + ′ = which is indeed the same as Eq. (37.21) with the primed coordinates replacing the unprimed, and a change of sign of u....
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online